Research Advances of Clinical Application of Oncolytic Viruses in Treatment of Gynecologic Cancers - Deng, Mingjing; Wang, Qi (Current Cancer Drug Targets, 2023)
Oncolytic viruses (OVs) have become one of the main strategies of cancer biotherapy. They are genetically engineered or naturally occurring viruses that selectively replicate and kill tumor cells without harming normal tissues. Gynecologic cancers have become a major health problem for women. OVs therapy plays an increasingly important role in the treatment of gynecological tumors with promising clinical effects. A variety of OVs is used in the treatment of gynecological tumors, either as single oncolytic virus therapy or in combination with other therapies. Some oncolytic virus therapies have entered early clinical trials and have shown favorable safety, clinical activity, and immune activation. The present study summarized the anti-tumor mechanism of OVs and their modifications. The study reviewed the latest clinical progress on the application of the OVs in the treatment of gynecologic cancers. The unique challenges in the development of the viruses as a novel drug for the treatment of gynecologic oncology were also discussed and their future prospects were elucidated.
Keywords: cancer biotherapy